Crystalline 2D Covalent Organic Framework Membranes for High-Flux Organic Solvent Nanofiltration - Shinde, Digambar B; Sheng, Guan; Li, Xiang; Ostwal, Mayur; Emwas, Abdul-Hamid; Huang, Kuo-Wei; Lai, Zhiping (Journal of the American Chemical Society, 2018)
Two-dimensional (2D) covalent organic framework (COF) materials have the most suitable microstructure for membrane applications in order to achieve both high flux and high selectivity. Here, we report the synthesis of a crystalline TFP-DHF 2D COF membrane constructed from two precursors of 1,3,5-triformylphloroglucinol (TFP) and 9,9-dihexylfluorene-2,7-diamine (DHF) through the Langmuir–Blodgett (LB) method, for the first timed. A single COF layer is precisely four unit cells thick and can be transferred to different support surfaces layer by layer. The TFP-DHF 2D COF membrane supported on an anodic aluminum oxide (AAO) porous support displayed remarkable permeabilities for both polar and nonpolar organic solvents, which were approximately 100 times higher than that of the amorphous membranes prepared by the same procedure and similar to that for the best of the reported polymer membranes. The transport mechanism through the TFP-DHF 2D COF membrane was found to be a viscous flow coupled with a strong slip boundary enhancement, which was also different from those of the amorphous polymer membranes. The membrane exhibited a steep molecular sieving with a molecular weight retention onset (MWRO) of approximately 600 Da and a molecular weight cutoff (MWCO) of approximately 900 Da. The substantial performance enhancement was attributed to the structural change from an amorphous structure to a well-defined ordered porous structure, which clearly demonstrated the high potential for the application of 2D COFs as the next generation of membrane materials.